Malatya’da Yaşayan 18-55 Yaş Arası Bireylerin Sağlık Okuryazarlığı Düzeylerinin İncelenmesi (Turkey Health Literacy Journal, 2024)
The purpose of this study is to determine the health literacy level of individuals aged 18-55 living in Malatya, Turkey. This descriptive and cross-sectional study was conducted in Malatya province of Turkey between December 2023 and January 2024. A total of 60 individuals aged between 18 and 55, who were able to communicate sufficiently and agreed to participate in the research, were included in the study. The Turkish Health Literacy Scale was used to collect research data. The data were collected via online survey method using the Google Forms application. In the study, it was found that 21.7% of the participants had sufficient to excellent health literacy levels. There were no significant differences in health literacy levels among age groups, gender, marital status, smoking status, and having health insurance. Additionally, the health literacy level was found to be significantly higher among those engaging in physical activity. As a result, this study has shown that the health literacy levels of individuals are quite low and it is crucial to raise them for the improvement of public health. Campaigns aimed at informing the public about how to access accurate health information, especially campaigns led by family physicians who are responsible for the population, and collaborative efforts involving input from the public to make written and verbal health information more understandable can be implemented to increase health literacy in the community.